(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The Earth’s surface is acquired by 71with water but only 3 of water can be used as potable water. Nowadays conservation of water is one of the basic principles of green building. The effort should be made to ensure that the fixtures that are used help in reduction of water consumption in residential buildings. Responsible use of fresh water means ensuring that all water consuming fixtures in public as well as residential areas are operating properly, with no leaks or drips, constantly running toilet tanks, or “ghost” flushes from automatic sensor based fixtures. A faucet leak of one drop per second can waste 3 7 gallons of water which is often paid for twice for the initial consumption and a second time in the form of waste water. This paper involves study of all the water efficient plumbing fixtures such as, taps, toilets, shower heads, urinals, etc. In addition to inspecting regularly for water leaks and responding immediately when receiving reports from residents, public housing authority (PHA) can achieve water saving by ensuring various water fixtures.